2003
DOI: 10.1002/ccd.10641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recanalization of chronic total occlusions on global and regional left ventricular function in patients with or without previous myocardial infarction

Abstract: Previous studies have demonstrated improvement of regional wall motion and global left ventricular function after successful recanalization of chronic total occlusion in coronary artery. However, the difference of benefits of recanalization between infarct site and noninfarct site is unknown. This study assessed the changes in left ventricular ejection fraction, regional wall motion after successful angioplasty of chronic total occlusions with or without previous myocardial infarction. This study also evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 99 publications
1
54
0
2
Order By: Relevance
“…Thus, we assumed that patients without previous MI with reduced LVEF may be associated with myocardial viability. Moreover, revascularization of CTO lesion could lead to a beneficial effect of recovering LV function in patients with good collateral circulation as our study results 15, 24…”
Section: Discussionsupporting
confidence: 54%
“…Thus, we assumed that patients without previous MI with reduced LVEF may be associated with myocardial viability. Moreover, revascularization of CTO lesion could lead to a beneficial effect of recovering LV function in patients with good collateral circulation as our study results 15, 24…”
Section: Discussionsupporting
confidence: 54%
“…Other observational studies have suggested additional benefits, including improvements in survival [1][2][3][4][5] and left ventricular ejection fraction [16][17][18]. In the absence of definitive randomized clinical trial data, further studies are warranted to delineate any potential survival advantage associated with CTO PCI.…”
Section: Discussionmentioning
confidence: 93%
“…[25][26][27] Successful revascularization of coronary CTO is associated with the improvement of left ventricular function in patients with angina pectoris or old myocardial infarction. [28][29][30] Recently, George and colleagues reported that successful CTO intervention was associated with a decrease in mortality as compared to unsuccessful CTO intervention using large registry data (n = 13,443). 31) Furthermore, Jang and colleagues reported the long-term survival benefit of CTO revascularization as compared to medical therapy using a propensity score-matched population.…”
Section: Discussionmentioning
confidence: 99%